Mechanical Stress Modulates Calcium-Activated-Chloride Currents in Differentiating Lens Cells - Ebihara, Lisa; Acharya, Pooja; Tong, Jun-Jie (Frontiers in Physiology, 2022)
During accommodation, the lens changes focus by altering its shape following contraction and relaxation of the ciliary muscle. At the cellular level, these changes in shape may be accompanied by fluid flow in and out of individual lens cells. We tested the hypothesis that some of this flow might be directly modulated by pressure-activated channels. In particular, we used the whole cell patch clamp technique to test whether calcium-activated-chloride channels (CaCCs) expressed in differentiating lens cells are activated by mechanical stimulation. Our results show that mechanical stress, produced by focally perfusing the lens cell at a constant rate, caused a significant increase in a chloride current that could be fully reversed by stopping perfusion. The time course of activation and recovery from activation of the flow-induced current occurred rapidly over a time frame similar to that of accommodation. The flow-induced current could be inhibited by the TMEM16A specific CaCC blocker, Ani9, suggesting that the affected current was predominantly due to TMEM16A chloride channels. The mechanism of action of mechanical stress did not appear to involve calcium influx through other mechanosensitive ion channels since removal of calcium from the bath solution failed to block the flow-induced chloride current. In conclusion, our results suggest that CaCCs in the lens can be rapidly and reversibly modulated by mechanical stress, consistent with their participation in regulation of volume in this organ.